2017
DOI: 10.5530/ijopp.10.3.37
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rational Drug Prescribing pattern in Geriatric Patients in Hyderabad Metropolitan

Abstract: Background: Polypharmacy and inappropriate prescriptions are prominent prescribing issues among geriatric patients. Beer's criteria, Drug-Drug interaction of common OTC drugs and WHO essential drug lists have been developed to assist in the reduction of potentially inappropriate medications prescribed to geriatric patients. Objective: This study was carried out to find out the rational prescription of drugs in the geriatric patients and to also investigate Polypharmacy. Methodology: A retrospective study on ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
3
2
Order By: Relevance
“…The percentage of male and female patients are 44.44% and 55.56% respectively. This finding is similar to the findings of study done by Nandagopal et al 8 Majority of the patients were in the age group of 61-70 years which was found similar to the study conducted by Bhaveshaikh et al 3 Patients with depressive disorders accounted for large majority (38.89%) of the patients attending the psychiatric OPD followed by schizophrenia and other psychotic disorders (30.56%) which is comparable to other studies done in India. 9,10 Analysis of prescription pattern as per the WHO prescribing indicators showed that the average number of drugs per prescription in this study was 2.69.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The percentage of male and female patients are 44.44% and 55.56% respectively. This finding is similar to the findings of study done by Nandagopal et al 8 Majority of the patients were in the age group of 61-70 years which was found similar to the study conducted by Bhaveshaikh et al 3 Patients with depressive disorders accounted for large majority (38.89%) of the patients attending the psychiatric OPD followed by schizophrenia and other psychotic disorders (30.56%) which is comparable to other studies done in India. 9,10 Analysis of prescription pattern as per the WHO prescribing indicators showed that the average number of drugs per prescription in this study was 2.69.…”
Section: Discussionsupporting
confidence: 91%
“…11 Giving drugs in the form of injections is not a common practice in psychiatry, barring emergency situations. The percentage of encounters with an injectable prescribed in this study was only 0.03% when compared to study done by Nandagopal et al 8 In this study out of the total 237 psychotropic drugs, 41.77% of psychotropic drugs were prescribed from NLEM (2015) and 17.72% from the WHO model list of essential medicines (2017). Compared to other reference studies, the percentage of drugs prescribed from EML was lower in the present study.…”
Section: Fdc Non Fdccontrasting
confidence: 68%
See 1 more Smart Citation
“…The average number of drugs per prescription in our study was 4.84 which are higher than the WHO optimal level of ≤3, indicating polypharmacy [20]. A higher rate of polypharmacy was seen in a study by Nandagopal et al, in Hyderabad, with an average of 7.02 [21]. Although the average in our study was lesser, it still requires that caution be taken to diminish the potentially higher risk of adverse health outcomes among the elderly.…”
Section: Discussioncontrasting
confidence: 62%
“…Our study showed that antihypertensives were the most commonly prescribed drug class followed by antidiabetics. In comparison to this, a study by Nandagopal et al revealed that antidiabetics (21.9%), followed by antibiotics (17.78%), were frequently prescribed [21]. According to the systems organ classification, 16.65% of the ADRs affected the metabolic and nutritional disorders.…”
Section: Discussionmentioning
confidence: 94%